Hydrogen Peroxide and Ferrous Sulphate Activated Wood Particles for Binderless Particleboard - Suhasman Suhasman; Muh. Y. Massijaya; Yusuf S. Hadi; Adi Santoso (Jurnal Ilmu dan Teknologi Kayu Tropis, 2010)
A series of study have been conducted to analyze  the  effect  of  pretreatments  and  particle sizes on physical  and  mechanical  properties of  binderless  particleboard  (BP). The BP made  of particles from sengon wood (Paraseranthes falcataria L Nielsen) and pine wood (Pinus merkusii Jungh et. de. Vriese) which passed through 10 mesh sieve, were used  to analyze  the effect of particle pretreatments. The pretreatments were: immersion in boiling water for 30 minutes; the immersion in boiling water followed  by oxidation  using  hydrogen  peroxide and ferrous sulphate; and oxidation using hydrogen peroxide and ferrous sulphate without immersion in boiling water. The results showed that the best  phisycal  and  mechanical properties was found in board made from sengon wood particle with oxidation using hydrogen peroxide without immersion in boiling water; It had the internal bond (IB) of 6.95 kgf cm-2 and the thickness swelling (TS) of 5.74%. In the next step, the sengon wood with several particles sizes namely; passed through 20 mesh, 10 mesh, 5 mesh, 2.5 mesh, and shaving were used to produced BP. The results indicated that the MOR decreases when the particle size increases, while the IB, MOE, and TS were relatively similar for all particle sizes.